The Influence of The 7P Marketing Mix Strategy and Digital Marketing on Car Purchasing Decisions at PT. Hadji Kalla Toyota Palopo Branch - Olgar; Suhandra Makkasauindra; kusdarianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Marketing mix helps companies design marketing strategies by paying attention to product, price, distribution, and promotion, while digital marketing uses digital technology to reach consumers directly, both work together to create brand awareness, influence consumer perceptions, and facilitate the purchasing process, influencing purchasing decisions consumers positively. This research aims to determine the influence of 7p marketing mix and digital marketing on car purchasing decisions at Pt. Hadji Kalla Toyota Palopo Branch, either partially or simultaneously. The research approach used in this research is a quantitative approach, namely a direct survey using data collection through questionnaires and observation. The research results show that (1) Marketing mix has no effect on purchasing decisions, with a calculated t value of the marketing mix variable of 1.201 < t table value (1.678) and a sig. 0.312 > 0.05. (2) Digital marketing has a significant positive effect on purchasing decisions, with a calculated t value for the digital marketing variable of 2.553 > t table value of 1.678 and a sig value. 0.014 < 0.05. And (3) Marketing mix and digital marketing simultaneously (together) have a significant effect on purchasing decisions with a calculated F value of 20.233 and a significance of 0.000 < 0.05.